The Influence of Pop Culture on Students' Islamic Identity: Moderation of Educational Environment Management at Thursina IIBS - Khabibah, Khilda Fitrotul; Firdausi, Kunti Mardiyatal; Yaqien, Nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study explores the influence of popular culture on the Islamic identity of students, particularly in the context of boarding school education. In the digital era, popular culture—manifested through K-pop, social media trends, and digital content—has become a dominant force shaping youth identity, often in contrast to Islamic values that emphasize modesty and spirituality. This research aims to analyze the direct impact of pop culture on students' Islamic identity and to examine the moderating role of educational environment management in Islamic boarding schools. A quantitative explanatory approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a sample of 114 female students from Thursina IIBS Malang. The findings reveal a significant negative relationship between exposure to pop culture and Islamic identity. However, the quality of educational environment management significantly moderates this relationship, reducing the negative impact. The results highlight that structured and value-based boarding school environments can function as a buffer against external cultural pressures. This study contributes to Islamic education management literature by providing empirical evidence on how institutional religious environments can reinforce student identity amidst global cultural trends.